Anti-Inflammatory and Antioxidant Properties of the Root Extract of Carissa Edulis (Forsk.) Vahl (Apocynaceae) (Journal of Science and Technology, 2016)
Root extracts of Carissa edulis (Forsk.) Vahl (Apocynaceae) are used for the treatment several pathological states including inflammatory disorders. The present study was undertaken to evaluate the effect of an alcoholic extract of C. edulis (CEE) on carrageenan-induced foot oedema in chicks. Also since free radicals and reactive oxygen species are implicated in inflammatory diseases, the anti-oxidant potential of extract was investigated in in vitro experimental models. Oral administration of CEE (30-300 mg kg-1 p.o.) significantly inhibited carrageenan-induced foot oedemas with a maximal inhibition of 53.8±8.2%. Similarly, the NSAID diclofenac (10-100 mg kg-1, i.p.) and the steroidal anti-inflammatory agent dexamethasone (0.3-3 mg kg-1, i.p ) reduced the total oedema with a maximal inhibition of 62.7±9.1% and 66.4±7.8% respectively. The extract also scavenged DPPH and prevented lipid peroxidation in rat brain homogenates. These results suggest that alcoholic extract of C. edulis exerts in vivo antiinflammatory activity after oral administration and also has antioxidant properties which may contribute to its activity.